Selective deprotonation of tetra[3, 4]thienylene in the presence of n-BuLi. Issue 6 (20th February 2017) - Li, Lu; Li, Bingbing; Li, Chunli; Ma, Zhiying; Xu, Li; Wang, Hua
Abstract : The sequential lithiation mechanism for the selective deprotonation of tetra[3, 4]thienylene (1 ) to formLi4 -1 in the present of n -BuLi in THF is investigated. Abstract : The sequential lithiation mechanism for the selective deprotonation of tetra[3, 4]thienylene (1 ) to formLi4 -1 in the present of n -BuLi in THF is investigated. The specific contralateral and ipsilateral selectivities of the lithiation sites in the different steps are explored. A series of tetra-substituted1 are obtained, via Li4 -1 with electrophiles, in good yields.